2017
DOI: 10.1002/biot.201700088
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Niche – Exploring Biomimetic Cues to Improve the Functionality of Hematopoietic Stem/Progenitor Cells

Abstract: The adult bone marrow (BM) niche is a complex entity where a homeostatic hematopoietic system is maintained through a dynamic crosstalk between different cellular and non-cellular players. Signaling mechanisms triggered by cell-cell, cell-extracellular matrix (ECM), cell-cytokine interactions, and local microenvironment parameters are involved in controlling quiescence, self-renewal, differentiation, and migration of hematopoietic stem/progenitor cells (HSPC). A promising strategy to more efficiently expand HS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 177 publications
1
20
0
2
Order By: Relevance
“…Bone marrow is both a hematopoietic organ and an immune organ. In the bone marrow microenvironment, hematopoietic stem cells differentiate into erythrocytes, granulocytes, platelets, and all kinds of immune cells including monocytes, dendritic cells, T cells, B cells, and natural killer (NK) cells ( 6 , 7 ). Among them, the monocytes/macrophages from hematopoietic lineage are osteoclast precursors ( 8 , 9 ).…”
Section: Osteoimmunology: Interaction Between the Skeletal And Immunementioning
confidence: 99%
“…Bone marrow is both a hematopoietic organ and an immune organ. In the bone marrow microenvironment, hematopoietic stem cells differentiate into erythrocytes, granulocytes, platelets, and all kinds of immune cells including monocytes, dendritic cells, T cells, B cells, and natural killer (NK) cells ( 6 , 7 ). Among them, the monocytes/macrophages from hematopoietic lineage are osteoclast precursors ( 8 , 9 ).…”
Section: Osteoimmunology: Interaction Between the Skeletal And Immunementioning
confidence: 99%
“…For example, the latest discoveries are antagonist of PPAR-gamma GW9662 (Guo et al, 2018), inhibitor JNK-IN-8 (Xiao et al, 2019), and so on. Moreover, it is found that some co-culture systems or materials could provide a suitable microenvironment for HSC expansion, such as coculture with polyvinyl alcohol (PVA) (Wilkinson et al, 2019), zwitterionic hydrogel (Bai et al, 2019), or mesenchymal stem/ stromal cells (Costa et al, 2018). Since HSCs are deemed to grow in hypoxic environment (Takubo et al, 2010), low oxygen also plays an important role in the in vitro expansion of HSC.…”
Section: Discussionmentioning
confidence: 99%
“…Вважається, що основні зміни клітинної композиції в органах імунної системи при стресі зумовлені перерозподілом мігруючих клітин і вираженістю апоптотичних процесів, які здійснюються в кістковому мозку і тимусі [16][17][18]. Мабуть, вирішальну роль у формуванні особливостей клітинних стресових реакцій і індукції регенерації імун ної системи відіграють гемопоетичні стовбурові клітини (ГСК) -родоначальники всіх гемопоетичних клітин, в тому числі тих, що є структурно-функціональною основою імунної системи [11][12][13]. Але зазначені питання слабо вивчені, хоча зрозуміло, їх висвітлення буде корисним і в теоретичному і практичному аспектах.…”
Section: вступunclassified